2020
DOI: 10.1186/s13287-020-02050-6
|View full text |Cite
|
Sign up to set email alerts
|

Human multipotent mesenchymal stromal cells cytokine priming promotes RAB27B-regulated secretion of small extracellular vesicles with immunomodulatory cargo

Abstract: Background The paracrine effects of multipotent mesenchymal stromal cells (MSCs) are mediated by their secretome composed by soluble factors (i.e., cytokines, growth factors, hormones) and extracellular vesicles (EVs). EVs promote intercellular communication, and the EV cargoes [e.g., proteins, soluble factors, microRNAs (miRNAs), messenger RNA (mRNA), DNA] reflect the molecular and functional characteristics of their parental cells. MSC-derived EVs (MSC-EVs) are currently evaluated as subcellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 82 publications
(78 reference statements)
6
52
0
Order By: Relevance
“…Overall, the interaction of these surface markers on exosomes with monocytes may improve the capacity of the educated monocytes to drive the tissue repair in ARS. It is important to note that TLR-4 stimulation by LPS is not the only method to prime MSCs and generate exosomes, as TNFα [ 20 22 ], IFNγ [ 22 , 23 ], and IL-1β [ 24 , 25 ] have also been shown as effective molecules for priming MSCs. A head-to-head comparison of MSC priming methodologies needs to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the interaction of these surface markers on exosomes with monocytes may improve the capacity of the educated monocytes to drive the tissue repair in ARS. It is important to note that TLR-4 stimulation by LPS is not the only method to prime MSCs and generate exosomes, as TNFα [ 20 22 ], IFNγ [ 22 , 23 ], and IL-1β [ 24 , 25 ] have also been shown as effective molecules for priming MSCs. A head-to-head comparison of MSC priming methodologies needs to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Bruno et al ( 37 ) revealed that exosomes play an important role in the paracrine effect of MSCs. MSC-derived exosomes with cytokines and growth factors, lipid signals, mRNA, and miRNA regulatory biomolecules have a biological function or information transfer function ( 38 , 39 ). They have similar functions to MSCs, including the promotion of tissue repair, immunosuppression, and neuroprotection.…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…However, methods for obtaining exosomes with high- quantity and high-purity remain a focus of research. Cytokine priming upregulated RAB27B siRNA in AD-MSCs, increasing their secretion of exosomes, which is a useful strategy for harvesting anti-inflammatory MSC-EVs for clinical applications ( 39 ). As mentioned earlier, gene editing is used to overexpress therapeutically effective molecules (such as mRNA, miRNA, and proteins) in MSCs to produce characteristic MSC-derived exosomes for different diseases.…”
Section: Dose Issues and Commercial Production Of Msc-derived Exosomementioning
confidence: 99%
“…In basal conditions, ASC released extracellular vesicles (EVs) with a preponderance of microRNAs (miRNAs) involved in OA cartilage and synovium protection (40%) over less than 10% of those involved in degenerative processes [ 5 ]. In addition, the EV cargo can be further modulated by preconditioning the mesenchymal stem cells (MSCs) with stimuli resembling the in vivo pathological environment [ 6 , 7 , 8 ]. ASCs inflammatory priming with interferon γ (IFNγ) determined a production of a 34.7% chondro-protective versus a 13.3% chondro-destructive miRNAs and a secretion of 26.2% versus 4.5% of M2- versus M1-macrophages-related miRNAs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%